THE EFFECT OF USING WATCHING FILM ON THE STUDENTS’ WRITING ABILITY AT THE TENTH GRADE OF SMA NEGERI 1 PANAI HULU - Alamanda, Niken; Daulay, Sholihatul Hamidah; Ismahani, Siti (Faculty of Tarbiyah nad Teacher Training, 2024)
This research aimed to examine the impact of using the film-watching method on tenth-grade students' achievement in writing narrative paragraphs at SMA Negeri 1 Panai Hulu. The study utilized an experimental research design, involving a population of 40 students from two classes. Data collection was conducted through a test, selecting classes X-A and X-B, each consisting of 20 students, as the sample. Class X-A served as the control group, while class X-B was the experimental group. The data was analyzed using statistical formulas and Microsoft Excel 2013, with a significance level set at 0.05. The results indicated that (1) students who used the film-watching method had a mean score of 52.25 with a standard deviation of 61.25 in writing narrative paragraphs, and (2) students using the conventional strategy had a mean score of 55.25 with a standard deviation of 70.26. The observed t-value was 4.881, which is greater than the critical t-value of 1.701 at a degree of freedom (df) = 38. This result led to the acceptance of the alternative hypothesis (Ha) and rejection of the null hypothesis (Ho), indicating a significant effect of the film-watching method on students’ ability to write narrative paragraphs.